2008
DOI: 10.1038/sj.bjp.0707523
|View full text |Cite
|
Sign up to set email alerts
|

CB2 receptor‐mediated migration of immune cells: it can go either way

Abstract: Though many studies have examined the role of CB 2 receptors in immune cell migration, it has been difficult to form definitive conclusions about the physiopathological role of these receptors in regulating immune responses and how this might be pharmacologically targeted for therapy. Do cannabinoids promote inflammation through the recruitment of immune cells, or reduce inflammation by interfering with the action of other chemoattractants? Is therapeutic intervention with an agonist or antagonist more appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
175
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(182 citation statements)
references
References 75 publications
7
175
0
Order By: Relevance
“…It was suggested that CB2 could act as a chemokine receptor and is therefore functionally involved in immune cell trafficking (41)(42)(43)(44). Here we showed that CB2 controls the recruitment of peripheral immune cells into the brain during ECM.…”
Section: Discussionmentioning
confidence: 52%
“…It was suggested that CB2 could act as a chemokine receptor and is therefore functionally involved in immune cell trafficking (41)(42)(43)(44). Here we showed that CB2 controls the recruitment of peripheral immune cells into the brain during ECM.…”
Section: Discussionmentioning
confidence: 52%
“…We favored this approach because eosinophils express the CB 2 receptor (26). Given the strong mRNA expression of CB 2 receptor in human eosinophils, it is possible that they were involved in the previously observed CB 2 expression by neutrophils (48)(49)(50). Additionally, it is noteworthy that the use of CB receptor Abs can be misleading (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we very recently provided evidence that rimonabant increases human sperm motility and viability (Aquila et al, 2010). Numerous findings suggested the role of the endocannabinoid system in the control of immunity, reporting the involvement of cannabinoid receptors in immune cell migration (Miller and Stella, 2008) and the efficacy of cannabinoid agonists as antinociceptive and anti-inflammatory agents (Guindon and Hohmann, 2008). We recently demonstrated the immunomodulatory and anti-inflammatory effects of rimonabant on peripheral blood mononuclear cells, showing inhibition of proliferation without induction of apoptosis, block of the G1/S phase of the cell cycle and modulation of the signalling kinases serine/threonine protein kinase Akt (Akt) and the extracellular signal regulated kinase, the transcription factor nuclear factor-kappa B (NF-kB) and its inhibitor (IkB) and the inducible enzymes cyclooxygenase-2 and inducible NO synthase .…”
Section: Abbreviationsmentioning
confidence: 99%